2009
DOI: 10.1016/j.nlm.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic mapping of rat forebrain and midbrain during delay and trace eyeblink conditioning

Abstract: While the essential neural circuitry for delay eyeblink conditioning has been largely identified, much of the neural circuitry for trace conditioning has yet to be determined. The major difference between delay and trace conditioning is a time gap between the presentation of the conditioned stimulus (CS) and the unconditioned stimulus (US) during trace conditioning. It is this time gap, which accounts for the additional memory component and may require extra neural structures, including hippocampus and prefron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…Brains were sectioned in a cryostat (20 μm) at −20°C. Every third section was collected on a cover slip and exposed for 5 days along with standards ( 14 C standards 10 × 0.02 mCi, American Radiolabeled Chemicals Inc., St Louis, MO) and exposed to X-ray film in a cassette (Kodak, Rochester, NY) (Boulanger Bertolus et al, 2014; Debiec & Sullivan, 2014; Plakke, Freeman, & Poremba, 2009; Sullivan & Wilson, 1995). …”
Section: Animals and Methodsmentioning
confidence: 99%
“…Brains were sectioned in a cryostat (20 μm) at −20°C. Every third section was collected on a cover slip and exposed for 5 days along with standards ( 14 C standards 10 × 0.02 mCi, American Radiolabeled Chemicals Inc., St Louis, MO) and exposed to X-ray film in a cassette (Kodak, Rochester, NY) (Boulanger Bertolus et al, 2014; Debiec & Sullivan, 2014; Plakke, Freeman, & Poremba, 2009; Sullivan & Wilson, 1995). …”
Section: Animals and Methodsmentioning
confidence: 99%
“…However, only a few researchers pay attention to its involvement in DEC. By using the methods of lateral amygdale lesion or muscimol (MSC) injection into the lateral amygdale, Sakamoto et al found [47] that the lateral amygdale plays important roles in the acquisition and expression of DEC in mice. Similarly, metabolic and lesion studies also show that the amygdala plays a role in DEC in rats [58][59][60]. Boele et al proposed the Amygdala-CerebellumDynamic-Conditioning Model (ACDC model), which indicates that the short-latency-response (SLR), a characteristic trace of the EBC in mice, may originate from the amygdala [17].…”
Section: The Neural Circuitry Of Dec In Micementioning
confidence: 99%
“…However, interest is growing, in part because contextual conditioning in rats serves as an animal model for human pathological anxiety such as in generalized anxiety disorder (Grillon et al, 2006;Zanoveli et al, 2007;Luyten et al, 2011b). So far, the neurocircuitry of conditioning has been studied primarily through lesion or inactivation experiments in rodents (often pretraining interventions) (Kim and Jung, 2006;Walker et al, 2009) and, to a lesser degree, using autoradiography or histochemistry techniques (Gonzalez-Lima and Scheich, 1986;Beck and Fibiger, 1995;Poremba et al, 1998;Plakke et al, 2009). To our knowledge, there are no published neuroimaging studies of conditioned rats, despite the obvious advantages of visualizing and quantifying metabolism of the intact brain in behaving animals.…”
Section: Introductionmentioning
confidence: 99%